STRATEGY FOR DEVELOPING FINANCIAL SELF-RELIANCE THROUGH FOOD SECURITY INDEPENDENT BUSINESS AT BOARDING SCHOOLS, BANYUASIN DISTRICT - ERDAH LITRIANI; M RASYID REDHO PRATAMA; FAKHRINA FAKHRINA; DISFA LIDIAN HANDAYANI; NURUL MUBAROK (Maqdis: Jurnal Kajian Ekonomi Islam, 2022)
This study aims to determine the strengths, weaknesses, opportunities and challenges of developing an independent food security business at the Sabilul Hasanah Islamic Boarding School in Mainan Village, Sembawa District, Banyuasin Regency in order to increase financial independence in Islamic boarding schools. This research design uses descriptive analysis with SWOT analysis with 4x4 diagrams, data collection techniques using interviews and observations. The results of this study : 1). Strength: food security (rice) is an abundant resource. 2) Weakness: lack of capital, business units that are not too developed, gaps between managers and students who have their own busy lives and activities. 3). Opportunity: food security business can meet the needs of Islamic boarding schools, can be marketed to realize financial independence, in the future this business program can develop to be bigger in meeting market fulfillment, the regulations that support it are very clear. 4) Threaths: the challenges faced are food entrepreneurs who already exist, consistency of suppliers of raw materials and prices, use of technology in marketing, trends in consumer behavior.